A Simple Polymicrobial Biofilm Keratinocyte Colonization Model for Exploring Interactions Between Commensals, Pathogens and Antimicrobials - Jordana-Lluch, Elena; Garcia, Vanina; Kingdon, Alexander D. H.; Singh, Nishant; Alexander, Cameron; Williams, Paul; Hardie, Kim R. (Frontiers in Microbiology, 2020)
Skin offers protection against external insults, with the skin microbiota playing a crucial defensive role against pathogens that gain access when the skin barrier is breached. Linkages between skin microbes, biofilms and disease have not been well established although single-species biofilm formation by skin microbiota in vitro has been extensively studied. Consequently, the purpose of this work was to optimize and validate a simple polymicrobial biofilm keratinocyte model for investigating commensal, pathogen and keratinocyte interactions and for evaluating therapeutic agents or health promoting interventions. The model incorporates the commensals (Staphylococcus epidermidis and Micrococcus luteus) and pathogens (Staphylococcus aureus and Pseudomonas aeruginosa) which form robust polymicrobial biofilms on immortalized keratinocytes (HaCat cells). We observed that the commensals reduce the damage caused to the keratinocyte monolayer by either pathogen. When the commensals were combined with P. aeruginosa and S. aureus, much thinner biofilms were observed than those formed by the pathogens alone. When P. aeruginosa was inoculated with S. epidermidis in the presence or absence of M. luteus, the commensals formed a layer between the keratinocytes and pathogen. Although S. aureus completely inhibited the growth of M. luteus in dual-species biofilms, inclusion of S. epidermidis in triple or quadruple species biofilms, enabled M. luteus to retain viability. Using this polymicrobial biofilm keratinocyte model, we demonstrate that a quorum sensing (QS) deficient S. aureus agr mutant, in contrast to the parent, failed to damage the keratinocyte monolayer unless supplied with the exogenous cognate autoinducing peptide. In addition, we show that treatment of the polymicrobial keratinocyte model with nanoparticles containing an inhibitor of the PQS QS system reduced biofilm thickness and P. aeruginosa localization in mono- and polymicrobial biofilms.